Anisotropic thermal-conductivity degradation in the phase-field method accounting for crack directionality. (15th March 2021) - Svolos, Lampros; Mourad, Hashem M.; Bronkhorst, Curt A.; Waisman, Haim
Abstract: Dynamic loads applied to metals may lead to brittle or ductile fracture depending on the imposed strain rates, material properties, and specimen geometry. With an increase in the applied velocity, brittle to ductile failure mode transition may also be observed. Furthermore, at high strain rates, ductile fracture may be preceded by shear bands, which are narrow bands of intense plastic deformation, typically accompanied by a significant rise in temperature. Reliable models are needed to predict the response of metals subject to dynamic loads. In particular, capturing the interplay between heat conduction and crack propagation using the phase-field fracture method is still an open research field. To accurately capture the heat transfer physics across crack surfaces, damage models degrading thermal-conductivity are necessary. While isotropic thermal-conductivity degradation models were proposed, they may lead to errors as they are indifferent to crack directionality. In our current work, a new anisotropic approach is proposed in which thermal-conductivity, which depends on the phase-field gradient, is degraded solely across the crack. It is shown that this approach improves the near-field approximation of temperature and heat flux compared with isotropic degradation, when taking the discontinuous crack solutions as reference. Additionally, the anisotropic degradation approach is implemented in a unified dynamic fracture model and a couple of examples demonstrate the viability of this approach. Highlights: Thermal-conductivity degradation is used to model heat-transfer physics across cracks. A new anisotropic approach that depends on the phase-field gradient is proposed. The temperature and heat flux errors are reduced compared with isotropic approaches. The solution to heat transfer problems with fracture becomes length scale insensitive. Inaccurate modeling of heat transfer may lead to poor capture of failure modes.